Peran Mediasi dari Presenteeism dan Workaholism dalam Pengaruh Job Insecurity terhadap Emotional Exhaustion - Latifah, Nandita Nury; Hendarsjah, Hidajat (Eksos, 2023)
The existence of a pandemic and government policies that require everyone to stay indoors has caused tourism, including hotels, to experience a decline in visitors. As a result, many of these hotels had to close and lay off the work of some of their employees. This causes the emergence of job insecurity among employees who are still working. Then many employees try to keep their jobs by practicing presenteeism and workaholism. However, this behavior will result in emotional exhaustion. This study aims to analyze the mediating role of presenteeism and workaholism in the relationship between jab insecurity and emotional exhaustion. This study used 103 respondents by taking respondents from hotel employees in Surakarta. Data analysis was carried out using the PLS (Partial Least Square) method with the smartPLS 4 program. Based on the results of the analysis it was concluded that job insecurity has a positive relationship with emotional exhaustion, presenteeism and workaholism are positive in the role of mediating the relationship between job insecurity and emotional exhaustion.